(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
The incidence of breast tumor increases every year in Indonesia. At present, breast tumors do not only attack the elderly, but also at young age. Some studies show factors associated with breast tumors. Therefore, this study aimed to study the association of the reproductive history with tumor incidence in young women in Indonesia in 2016. This study used a cross-sectional study design and was conducted in December 2018-January 2019 in the Faculty of Public Health of Universitas Indonesia using secondary data from the Riset PTM 2016 (Non-communicable Disease Research 2016). The population in this study were all respondents of the 2016 PTM Research. The sample was 14,891 respondents (total sampling) aged under 40 years who meet the inclusion and exclusion criteria. The variables used in this study were independent variables consisting of age of menarche, age of first birth, marital status, breasfeeding history, the use of hormonal contraception; and the dependent variable is the incidence of breast tumors. The data was analyzed by chi square and logistic regression test. The results showed an association between menarche age (OR=1,269), marital status (OR=1,353), breasteeding history (OR=1,295), and the use of hormonal contraception more than 5 years (OR=1,113) with breast tumors in young women in Indonesia.